The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/land11050626
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Subsurface Drainage in the Sugarcane Crop under Different Spacing and Drain Depths

Abstract: Agricultural land drainage is an instrument for growing production and a tool for the conservation of land resources. The performance of land drainage systems is thus critical for achieving sustainable agricultural production Recently, many types of software have been developed in this field for modeling and simulating the performance of these systems. SISDRENA is a simulation model of the performance of underground drainage systems. The main objectives of this paper are to simulate different combination of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 73 publications
1
0
0
Order By: Relevance
“…Good water drainage canals are very important for sugarcane plantations because stagnant water causes root rot [66]. Several studies have also revealed that it has a significant impact on productivity and plays a role in the conservation of agricultural land [67]. These are in accordance with the previous study that drainage is very important for sugarcane plants because the drainage system can prevent the loss of nutrients due to soil erosion [68].…”
Section: Discussionsupporting
confidence: 81%
“…Good water drainage canals are very important for sugarcane plantations because stagnant water causes root rot [66]. Several studies have also revealed that it has a significant impact on productivity and plays a role in the conservation of agricultural land [67]. These are in accordance with the previous study that drainage is very important for sugarcane plants because the drainage system can prevent the loss of nutrients due to soil erosion [68].…”
Section: Discussionsupporting
confidence: 81%